2009
DOI: 10.1007/s11468-009-9103-5
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Metal-Enhanced Fluorescence Using a Liquid–Liquid Droplet Micromixer in a Disposable Poly(Methyl Methacrylate) Microchip

Abstract: Solution-based metal-enhanced fluorescence of near-infrared fluorophores in a poly(methyl methacrylate) microchip is studied. A liquid-liquid droplet micromixer is used for rapid mixing of fluorophores with silver nanoparticles while maintaining discrete packets of known analytes for reproducible quantitative analysis. Nanoparticle aggregation within the microchip is controlled by individually adjusting salt concentration, colloid concentration, and mixing efficiency. Results identify an optimal salt concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…By making use of the plasmonic enhancement of nanorods and nanoshells, Halas and co-workers have demonstrated that NIR dyes can be as efficient as organic dye molecules in the visible range (Bardhan et al 2009; Tam et al 2007). Recently, metal enhanced fluorescence has been applied in microfluidic chips to enhance the detection efficiency of NIR dye labels (Furtaw et al 2009). Metal nanoparticles have also been employed in therapeutic applications, such as photothermal cancer therapy.…”
Section: Localized Surface Plasmonsmentioning
confidence: 99%
“…By making use of the plasmonic enhancement of nanorods and nanoshells, Halas and co-workers have demonstrated that NIR dyes can be as efficient as organic dye molecules in the visible range (Bardhan et al 2009; Tam et al 2007). Recently, metal enhanced fluorescence has been applied in microfluidic chips to enhance the detection efficiency of NIR dye labels (Furtaw et al 2009). Metal nanoparticles have also been employed in therapeutic applications, such as photothermal cancer therapy.…”
Section: Localized Surface Plasmonsmentioning
confidence: 99%
“…Third, aggregation has been known to broaden and red-shift the resonant frequency of AgNPs by enabling multipole plasmon modes and thus increases the interaction with NIR light [see Figure b]. Aggregation of AgNP has also been shown to generate small, localized, enhanced electromagnetic fields, known as “hot spots”, thereby enabling significant SEF of appropriately located fluorophores. ,,, Therefore, a combination of enhanced near-field due to aggregation with low far-field losses and the maximized quality factor makes NIR-SEF with AgNPs in solution a powerful technology.…”
Section: Resultsmentioning
confidence: 99%
“…When certain criteria are met, the radiative decay dominates nonradiative processes, which along with the enhanced excitation rate can significantly increase the quantum yield. Enhanced signal intensity from SEF along with lower background via NIR fluorophores has been shown to provide substantial improvement to fluorescence sensitivity. , NIR-SEF has been demonstrated previously with gold nanostructures on surfaces, gold nanoparticles in solution, silver nanostructures on surfaces, ,,, and silver nanoparticles in solution. , …”
Section: Introductionmentioning
confidence: 90%
“…The improved local electromagnetic field at an interface was confirmed to greatly excite neighboring atoms, molecules and nanomaterials thus enhancing fluorescence, Raleigh scatting and Raman scatting 21 . If the interface is located on a smaller surface 22 , the interfacial fluorescence would be further enhanced by the additionally surficial activation energy of quantum dots 23,24 , nanotubes 25 , nanoparticles [26][27][28] , nanoclusters 29 and 2 dimensional nanoparticle sheets 30 as well. However, our current knowledge of liquid interface enhanced fluorescence is limited because of difficulties related to observing the liquidliquid interface.…”
mentioning
confidence: 99%
“…In addition, the enhanced fluorescence can be further intensified by a surficial plasma at the interface, which excites the closed fluorophores or dipoles, thus enhancing the interfacial fluorescence. Investigations of plasmatic enhanced fluorescence have mainly focused on metal surface enhanced fluorescence. The improved local electromagnetic field at an interface was confirmed to greatly excite neighboring atoms, molecules, and nanomaterials and thus enhance fluorescence, Raleigh scattering, and Raman scattering . If the interface is located on a smaller surface, the interfacial fluorescence would be further enhanced by the additional surficial activation energy of quantum dots, , nanotubes, nanoparticles, nanoclusters, and 2-dimensional nanoparticle sheets as well. However, our current knowledge of liquid interface enhanced fluorescence is limited because of difficulties related to observing the liquid–liquid interface.…”
mentioning
confidence: 99%